A Case of Severe Aplastic Anemia Complicated with Liver Cirrhosis Induced by Post-Transfusion Hepatitis and Secondary Hemochromatosis - UTSUNOMIYA, Yasushi; MATSUSHITA, Eiji; TSUJI, Yasuhiro; NAKAJIMA, Masahiro; HARADA, Yuichirou; TANAKA, Kiyoshi; ISHITANI, Nobuo; HOSHIKA, Tadataka; OKADA, Takayoshi; NISHIKAWA, Kenhiti (The Japanese Journal of Pediatric Hematology, 1990)
We reported a case of a 17-year-old boy with severe aplastic anemia complicated with liver cirrhosis induced by post-transfusion hepatitis and secondary hemochromatosis. B3cause of refractory anemia, he received many blood transfusions, and died of hepatic failure. At autopsy a large amount of hemosiderin deposition was found in the liver, pancreas, spleen, adrenal cortices, thyroid gland, stomach, and colon. There was marked lymphocyte infiltration in the liver, which was considered to be due to hepatitis. The liver also showed mild fibrosis with hemosiderin deposition in Kupffer cells. It is suggested that post-transfusion hepatitis was aggravated by secondary hemochromatosis, and developed liver cirrhosis.